Foreign aid, debt and technical assistance in small open economies: the ECCB case - Williams, Arthur (Eastern Caribbean Central Bank [Basseterre)KN, 1991)
Gives an overview of the economies of the Eastern Caribbean Central Bank Region during the 1980s. Looks at external assistance to the region which comprises mainly of grantsl loans and technical assistance. Concludes that the underlying structure of the economy has not changed significantly despite problems encountered in the seventies and eighties. The process of economic transformation has been slow as the efforts towards diversification have not taken root as yet.